Sleepyheads - Howatt, Sandra J.; Wan, Joyce (New York : Beach Lane Books, 2014)
"Drowsy animal babies snuggle in trees, caves, weeds, and on waves, but one sleepyhead isn't yet in his bed"--
Ages 4-8.
Keywords: Stories in rhyme; Bedtime -- Fiction; Sleep -- Fiction; Babies -- Fiction; Animals -- Sleep behavior -- Fiction; Animals -- Infancy -- Fiction